Analisis Pelaksanaan Fasilitas Preservasi Arsip Statis Guna Meningkatkan Tata Kelola Bidang Kearsipan Pemerintahan - Ramadhan, Ndaru; Adinda FA, Jovanscha Qisty (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
This research discusses the implementation of static archive preservation facilitation at the Dinas Perpustakaan dan Arsip Daerah Daerah Istimewa Yogyakarta. This research aims to find out and analyze how the facilitation of static archive preservation is implemented and the obstacles in the Dinas Perpustakaan dan Arsip Daerah Daerah Istimewa Yogyakarta. The research method used is a qualitative method with a descriptive approach. The subjects in this research are young archivists and advanced archivists, while the object of this research is the implementation of static archive preservation facilitation at the Dinas Perpustakaan dan Arsip Daerah Daerah Istimewa Yogyakarta. The data sources in this research are primary data obtained through interviews with informants and secondary data obtained through literature reviews. The collection techniques used in this research are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusions. The results of this research show that the implementation of preservation facilitation at the Dinas Perpustakaan dan Arsip Daerah Daerah Istimewa Yogyakarta includes several stages, namely sorting, coding, checking ink for cartographic archives, making deacidification fluid, applying Methyl Cellulose glue, drying archives, pressing archives, and storing archives. However, there are still several obstacles, namely the condition of the archives, which are damaged or parts of the archives are incomplete; limited human resources, which affect the division of employee work; limited facilities and infrastructure in the form of drying places; and budget limitations, which cause the number of archives to be preserved to be limited.